Ethnic Entrepreneurs and Political Mobilization: Exploring a Case of Tharu-Pahadi Conflict - Bhattarai, Ishwari (Dhaulagiri Journal of Sociology and Anthropology, 2015)
Nepalese society today is witnessing an unprecedented sharpening of ethnic boundaries. In the last couple of decades or so, there have been growing instances of inter-ethnic conflict and clashes. The clash among the Tharus and Pahadi (Bahun-Chhetri) communities that took place in the month of May, 2012 in the Nawalparasi district is one such example. Borrowing the conceptual idea from Fredreick Barth (1995) who critically engages with the question of culture, ethnicity, and contemporary nature of ethnic mobilization, this paper seeks to explore how such conflicts are an epiphenomena of tactical moves carried out what he calls as ‘middle echelon politicians’. Through the qualitative data collected with the help of open-ended interviews and couple of other illustrations, this paper argues that, the contemporary character of ethnic mobilizations in some way or the other, are manipulated by ethnic entrepreneurs who politicize cultural differences, ethnic sentiments, and collective backwardness which often result in violent confrontations. Despite the Tharus being diverse and sharply divided in terms of political allegiance and electoral behavior, the leaders or activists use politics of cultural difference, and attempt to mitigate internal differences, to present a consolidated picture of ethnic unity. Through such actions ethnic leaders or activists selectively mobilize ethnic sentiments and symbols in order to motivate members of an ethnic group and also assume leadership position at both local and national levels.